Evaluation of the effects of initial deviatoric stress and cyclic stress amplitude on liquefaction potential of loose and medium-dense sands: An energy-based method. Issue 136 (September 2020) - Ni, Xueqian; Ye, Bin; Cheng, Zirui; Ye, Guanlin
Abstract: The energy-based method is a promising tool for evaluating soil liquefaction potential. In this study, the effects of initial deviatoric stress ( q s ) and cyclic stress amplitude ( q cyc ) on soil liquefaction potential in undrained cyclic triaxial tests were evaluated using the energy-based method. The testing results indicate that the required dissipated energy for the onset of liquefaction is influenced by both q cyc and q s for a loose sand, while it is only affected by q s for a medium-dense sand. For both loose and medium-dense sands, there exists an approximately unique relationship between the residual excess pore water pressure ratio and the normalized dissipated energy ( W n ) during cyclic loadings, independent of q cyc and q s . The relationship between the double-amplitude axial strain and the W n is influenced not only by initial conditions but also by loading conditions. The evaluation of the effects of the various factors on the liquefaction potential based on the energy-based method provides insight into the liquefaction resistance for both loose and medium-dense sands. Highlights: The criteria of the onset of liquefaction in loose and medium dense sands are differentiated. The influences of some factors on the required dissipated energy for the onset of liquefaction are evaluated. The variations of the excess pore water pressure ratio and the axial strain with the dissipated energy are investigated.